Eco-Premium or Eco-Penalty? Eco-Labels and Quality in the Organic Wine Market. (February 2017) - Delmas, Magali A.; Lessem, Neil
Eco-labels emphasize information disclosure as a tool to induce environmentally friendly behaviors by both firms and consumers. The goal of eco-labels is to reduce information asymmetry between producers and consumers over the environmental attributes of a product or service. However, by focusing on this information asymmetry, rather than on how the label meets consumer needs, eco-labels may send irrelevant, confusing, or even detrimental messages to consumers. In this article, the authors investigate how the environmental signal of eco-labels interacts with product characteristics such as brand, quality, and price. In a discrete choice experiment, the authors examine consumer response to two similar eco-labels for wine, one associated with a quality reduction and the other not. The results show that respondents preferred both eco-labeled wines over otherwise identical conventional counterparts when the price was lower and the wine was from a lower quality region. However, they preferred conventional, more expensive wine from a high-quality region. This preference indicates that respondents not only obtain some warm glow value from eco-labeled wine but also possibly interpret eco-labeling as a signal of lower quality. This relationship held across both types of eco-labels, meaning that consumers did not understand the difference between them. This research contributes to the literature on information disclosure policies by highlighting important elements for effective eco-labels. These elements include consumer awareness and understanding of the eco-label, and consumer willingness to pay for an eco-labeled product. The results emphasize the need to create eco-labels that communicate clearly both the environmental attributes and the private benefits associated with them.